Face centred cubic multi-component equiatomic solid solutions in the Au-Cu-Ni-Pd-Pt system - Freudenberger, Jens; Rafaja, David; Geissler, David; Giebeler, Lars; Ullrich, Christiane; Kauffmann, Alexander; Heilmaier, Martin; Nielsch, Kornelius (Metals, 2017)
A single-phase solid solution is observed in quaternary and quinary alloys obtained from gold, copper, nickel, palladium and platinum. The lattice parameters of the alloys follow the linear rule of mixture when considering the lattice parameters of the elements and their concentration. The elements are a priori not homogeneously distributed within the respective alloys resulting in segregations. These segregations cause a large broadening of X-ray lines, which is accessed in the present article. This correlation is visualized by the help of local element mappings utilizing scanning electron microscopy including energy dispersive X-ray analysis and their quantitative analysis.
CRIS-Team Scopus Importer:2022-04-14
Keywords: High entropy alloy; Segregation; Solid solution; XRD line broadening